2021
DOI: 10.2174/1574886315666200805103053
|View full text |Cite
|
Sign up to set email alerts
|

Use of Sodium-Glucose Co-Transporter-2-Inhibitors (SGLT2-Is) and Risk of Lower Limb Amputation

Abstract: Background: Treatment with sodium-glucose co-transporter-2-inhibitors (SGLT2-Is), such as canagliflozin, has been associated with an increased risk of lower limb amputations (LLAs) in type 2 diabetes mellitus (T2DM). However, conflicting results have been reported for different SGLT2-Is and the underlying mechanism is unclear. Objective: To investigate the risk of LLA and diabetic foot ulcer with SGLT2-I use compared to other anti-diabetic drugs and to explore hypovolemia as a potential underlying mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 31 publications
1
7
1
Order By: Relevance
“…1.61 per 1,000 person-years; HR: 0.87; 95% CI: 0.72–1.06; p = 0.18; I 2 = 79.8%; Supplementary Appendix S5.5 ). The prevalence of PVD in these studies ranged from 0% to 8.1% ( Ryan et al, 2018 ; Yang et al, 2019 ; Yuan et al, 2018; Fralick et al, 2020 ; Yu et al, 2020 ; Paul et al, 2021 ; Werkman et al, 2021 ; Patorno et al, 2022 ). Similarly, when the baseline PVD prevalence was greater than 10% (768 events among 264,885 patients vs .…”
Section: Resultsmentioning
confidence: 93%
“…1.61 per 1,000 person-years; HR: 0.87; 95% CI: 0.72–1.06; p = 0.18; I 2 = 79.8%; Supplementary Appendix S5.5 ). The prevalence of PVD in these studies ranged from 0% to 8.1% ( Ryan et al, 2018 ; Yang et al, 2019 ; Yuan et al, 2018; Fralick et al, 2020 ; Yu et al, 2020 ; Paul et al, 2021 ; Werkman et al, 2021 ; Patorno et al, 2022 ). Similarly, when the baseline PVD prevalence was greater than 10% (768 events among 264,885 patients vs .…”
Section: Resultsmentioning
confidence: 93%
“…SGLT-2s reduced the risk of dialysis, transplantation, or death due to kidney disease in individuals with T2DM, with or without basic renal disease, and provided protection against acute kidney injury [45][46][47]. The use of SGLT-2s was not associated with an increased risk of fracture and amputation compared with other antidiabetics [44,[48][49][50]. Volume depletion is another major concern, not consistent with recent studies, which showed signi cant differences between SGLT-2s and other oral hypoglycaemic agents in volume depletion events [51][52][53], perhaps because of individualised dosing of SGLT-2s.…”
Section: Discussionmentioning
confidence: 98%
“…56 However, a cohort study using data from the Clinical Practice Research Datalink GOLD (2013–2019) demonstrated using SGLT2i drugs in 51,847 patients, with or without signs of hypovolemia, was not associated with an increased risk of lower-limb amputation. 57…”
Section: Discussionmentioning
confidence: 99%
“…56 However, a cohort study using data from the Clinical Practice Research Datalink GOLD (2013-2019) demonstrated using SGLT2i drugs in 51,847 patients, with or without signs of hypovolemia, was not associated with an increased risk of lower-limb amputation. 57 Six observational studies using the Truven MarketScan health claims database from the USA were conducted to investigate the effect of SGLT2i drugs use on amputation risk. The results vary from no difference in amputation risk with canagliflozin compared with non-SGLT2i glucose-lowering agents in three studies [58][59][60] and lower amputation risk with SGLT2i drugs (where canagliflozin therapy comprised 70% of SGLT2i use) compared with sulfonylurea agents, but not compared to DPP-4 inhibitors in two studies 61,62 and only one study that showed a higher amputation risk with SGLT2i drugs compared with DPP-4 inhibitors, but not compared with sulfonylurea agents or non-metformin, non-SGLT2i glucose-lowering agents.…”
Section: Sodium-glucose Cotransporter 2 Inhibitor (Sglt2i)mentioning
confidence: 99%